De jaleco branco : a relação com o saber dos estudantes de medicina de uma universidade privada - Vieira, Karina Sales (2022)
This study has as its main goal to analyze Medical School students from a private college relation with knowledge. And, in additions, as students whose families belong to higher social class. The students who make up the researched population are 31 academics of Ages College’s Medical School; which monthly payment is of 8.887,73R$. From the premise that learning has a different meaning to each individual because of one’s singularity, it was specially sought to delineate the socioeconomical profile of Medicine’s undergraduates, to know the epistemic dimension of these students’ relationship with knowledge, what they say they learn, in which conditions, ways and specificities; to recognize the identity dimension of medical students’ connection with knowledge, and which projects they develop for the future; finally, to verify the social dimension of medical students, characterizing the conditions and social relations of existence. We conducted the research mainly anchored in the studies of Charlot and Gonzalez and Branco and inspired by the phenomenological-hermeneutic method. The data were produced by the application of a questionnaire, balance of knowledge and semi-structured interviews. The study pointed to a profile of young, female, white, single students, with basic education predominantly in private schools, from higher social strata whose parents have a good level of education. Still revealed that The connection with learning in medical training is marked by the desire for personal fulfillment and based on the diploma, entering the job market, achieving financial stability, and much more than that, being able to care, cure and offer support. In this context, it seems that medical training fulfills its mission of training doctors with technical knowledge and a human dimension, as they prefer intellectual and academic learning and relational and affective learning. On the other hand, medical training is experienced under pressure, social and family isolation, exhausting routine, excess content, and sometimes psychological suffering; still, face the challenge of Problem Based Learning (PBL). Finally, dressed in white coats, submerged in dreams and expectations, they believe in effort and determination as elements for student success and for the formation of a human doctor who can treat people, not just diseases.